2019
DOI: 10.1186/s12891-019-2870-z
|View full text |Cite
|
Sign up to set email alerts
|

Do the radiological changes seen at mid term follow up of stemless shoulder prosthesis affect outcome?

Abstract: BackgroundThe Eclipse® (Eclipse® is a trademark of Arthrex, Naples, Florida) stemless shoulder prosthesis offers the surgeon the advantage of bone stock preservation and at the same time avoids the drawbacks of a resurfacing arthroplasty. Previous studies have shown radiographic changes on serial follow up of the Eclipse prosthesis. This study attempts to assess the significance of these radiographic changes and effect of cuff related pathology on the mid-term outcome of the Eclipse prosthesis.MethodsBetween J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…It is feasible that RLLs represent stress shielding due to load transfer passing predominantly through the cage screw and this is something seen by other surgeons using the Eclipse implant. 20,23 When comparing our results with those available for other stemless anatomical TSA designs, we again found ours to be higher than those reported by the designers of those implants. Huguet et al, 24 from the TESS Group, found no radiolucencies at a mean of 45 months' follow-up in his series of 63 patients.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…It is feasible that RLLs represent stress shielding due to load transfer passing predominantly through the cage screw and this is something seen by other surgeons using the Eclipse implant. 20,23 When comparing our results with those available for other stemless anatomical TSA designs, we again found ours to be higher than those reported by the designers of those implants. Huguet et al, 24 from the TESS Group, found no radiolucencies at a mean of 45 months' follow-up in his series of 63 patients.…”
Section: Discussionsupporting
confidence: 44%
“…Our strict criteria for radiological inclusion reduces our total number of included radiographs, and may be responsible for our higher incidence of RLLs. Moursy et al 20 noted a similarly higher rate of RLLs than Habermeyer et al 8 in their small series, when reviewing mid-term results. They also reviewed stress-shielding using MRI studies but found neither RLLs nor stress-shielding to affect patient outcome.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The clinical significance of stress shielding under a stemless implant is unknown and could possibly be explained by a radiographic phenomenon rather than actual bone loss. 14,20,24,40 We did not include evaluation of axillary radiographs in this study as the majority were performed at one of several outside community radiology clinics and inconsistency in arm positioning did not allow for reliable grading with this method. This also limited our ability to evaluate ''recentering'' the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 99%